3D-SiC decorated with SiC whiskers: Chemical vapor infiltration on the porous 3D-SiC lattices derived from polycarbosilane-based suspensions. Issue 5 (1st April 2020) - Xiong, Huiwen; Chen, Hehao; Chen, Zhaoke; Xiong, Xiang; Zhang, Dou; Zhou, Kechao
Abstract: SiCw /3D-SiC composites were fabricated by chemical vapor infiltration (CVI) of the 3D SiC lattices, which were prepared via direct ink writing of polycarbosilane-based suspensions. Microstructure, composition and tensile strength of the composites were investigated. Curing and pyrolysis temperature greatly affected the shrinkage, weight loss, density and composition of the 3D SiC. Although sound structure with spanning feature was achieved, cracks and pores in 3D SiC were formed during the pyrolysis owing to the large shrinkage. CVI process decreased the porosity and led to fully dense surface of the SiCw /3D-SiC composites. After 60h of CVI, short β-SiC fibres or long SiC whiskers were deposited in the structural spacing of 3D lattices or spherical pores inside the filaments, respectively. The tensile strength of the composites by CVI increased from 3.3 MPa to 15.7 MPa (20 h) and 47.3 MPa (60 h), due to the high strength of dense CVI layers and in-situ formed SiC whiskers in pores. This work showed a way to strengthen the 3D SiC with in-situ formed whiskers via the polymer precursor routes.